Improved segmented CRC assisted puncturing Polar decoding - Yanhong NI; Xiangxiong LOU; Jianrong BAO (Dianxin kexue)
A segmented cyclic redundancy check (CRC) assisted decoding algorithm was proposed.This method makes use of the high parallelism of BP decoding and the high reliability of CRC verification,and uniformly or proportionally disperses CRC verification bits into the original information bits.Simulation results show that when the code length N is 1 024 and the SNR is 3.5 dB,the average iterations of segmented CRC（2,16×2）and CRC (2,24+8) are 2.7 and 2.8 times less than those of G matrix based decoding.When the code length M is 896,the two segmented methods with a bit error rate of 10-5obtained about 0.7 dB gain compared with the non-CRC assisted BP puncturing decoding.